Kajian Humor Pada Dakwah Kyai Anwar Zahid - Nusaibah Samiyah Iroyna; Adzan Ninggar; Nur Anisa Gama Windianti (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2023)
The use of humor in preaching is something that is practiced by many da'i either through the pulpit directly or through internet media such as YouTube. Humor can be an allure for preachers because it can bring a fun atmosphere to their da'wah activities. Therefore a da'i needs to adjust the dose of humor in each of his da'wah activities. In this article, the author examines the study of humor in da'wah from one of the leading preachers, especially on the island of Java, namely KH. Anwar Zahid. KH. Anwar Zahid is famous for every joke in his da'wah activities which are mostly themed on everyday events experienced by the community, not infrequently he also brings sarcasm humor and even witty humor using academic sentences depending on who the mad'u attend.